Multiple Roles and Stress on Students of Transfer Program of 2019 STIKES Bina Usada Bali Nursing Study Program - Nina Rismawati Hakim; I Gede Wirajaya (Universitas STRADA Indonesia, 2021)
Nurse is currently being required to enhance their professional level of competency and qualification. This particular condition has formed a multiple type of nursing roles (education-profession-family). The adaptation in the previously said multiple roles, i.e. student-profession-family, is a requirement for the nursing students of transfer program. This research is using cross sectional design. The data were collected through questionnaire distributed to 134 nursing students of transfer program of STIKES Bina Usada Bali. The result showed 107 students (79.0%) of having a low degree of multiple roles where 87 students (64.9%) had a low level of stress. The result of the analysis with the Spearman’s Rank Test equaled to 0.683, indicated a strong level of the relation with the value of p = 0.0001 lower than ɑ = 0.05 (p<0.05). The students with multiple roles are supposed to effectively manage their stress in order to properly carry out the roles.